Narrativas de professoras mães: (des) encontros entre o dever-ser e o devir-nômade - Backes, Débora dos Reis Silva (2023)
The present study proposes to investigate the relationship between mothering and teaching by mapping the plane of collective forces through a moving map. Perceiving the narrative as a strong possibility for research in the field of Education, the proposal runs through post-structuralist perspectives that, in its multiple accesses, promotes several displacements, allowing us to transgress practices that we assume are permanent and meanings that seem fixed to us. Through the thought of Gilles Deleuze and Félix Guattari about Devir Nômade, as well as through the thought of Friedrich Nietzsche about Morality, adopting cartography as a methodological path, this research intends to abandon the reference to the representational model, towards the escape of copying and reproduction, making possible the production of oneself from new aesthetics of existence. Thus, the intention was to denaturalize the historical linearity of events in order to approach discontinuities and value destabilizations. The interview approach aligns with the possibility of allowing freer collections, where responses are not conditioned to a standardization of alternatives. Faced with the movement of narrating about oneself, the research aimed to think about the relationship between mothering and teaching through the narratives of teaching mothers working in public schools in Aracaju, Sergipe, apprehending their experiences from the decision to study Education, the training path, the mothering , her strategies for combining personal and professional life and how these elements reflect in her movement of teaching and mothering in order to tension produced subjectivities. We were interested in observing the dismantling of some worlds and the formation of others, the transmutation of constituted forms. Based on these women's narratives, we were able to compose with a landscape designed by vibrating bodies affected and that affect between collectivities and social movements, visualizing confrontations with historical strata and thinking about other movements based on forces, visible or not, to scrutinize how regularities are destabilized and keep up with new developments.